2021
DOI: 10.1038/s41433-021-01604-z
|View full text |Cite
|
Sign up to set email alerts
|

Negative electroretinograms: genetic and acquired causes, diagnostic approaches and physiological insights

Abstract: The dark-adapted human electroretinogram (ERG) response to a standard bright flash includes a negative-going a-wave followed by a positive-going b-wave that crosses the baseline. An electronegative waveform (or negative ERG) results when the b-wave is selectively reduced such that the ERG fails to cross the baseline following the a-wave. In the context of a normally sized a-wave, it indicates a site of retinal dysfunction occurring after phototransduction (commonly at the photoreceptor to bipolar cell synapse)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 97 publications
0
32
0
Order By: Relevance
“…The b-wave, on the other hand, which represents the activity of the interneurons, showed a significantly reduced response in both scotopic and photopic conditions, starting from the age of 6 M and deteriorating over age ( Figure 4 A). A selective reduction in the b-wave is also called a negative ERG [ 38 , 39 ]. The b-wave originates from the depolarization of the inner retinal cell types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The b-wave, on the other hand, which represents the activity of the interneurons, showed a significantly reduced response in both scotopic and photopic conditions, starting from the age of 6 M and deteriorating over age ( Figure 4 A). A selective reduction in the b-wave is also called a negative ERG [ 38 , 39 ]. The b-wave originates from the depolarization of the inner retinal cell types.…”
Section: Resultsmentioning
confidence: 99%
“…The negative ERG, i.e., impaired b-waves despite normal a-waves, in Crx-Mfp2 −/− and Crx-Pex5 −/− mice also points to a hampered signal transduction at the level of photoreceptor–bipolar cells. In other mouse models negative ERGs were related to either presynaptic defects in photoreceptor terminals or postsynaptic defects in bipolar cells [ 38 , 39 , 41 ]. Presynaptic defects result for example from incorrect assembly or functioning of the photoreceptor ribbon synapse, such as in Bsn Ex4/5 , Ribeye −/− and Crx-Pomt1 −/− mutant mice [ 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also analyzed responses from a second patient with cCSNB from another genetic cause (biallelic pathogenic variants in the TRPM1 gene) ( 22 25 ). This patient showed the same shape of responses to the various stimuli as seen in the patient with NYX -associated cCSNB (illustrated in SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…found that mice with nyx mutations were initially more hyperopic than wild-type mice, but were more susceptible to form deprivation myopia ( 36 ). In humans with congenital ON-pathway loss (complete CSNB), high myopia is usually seen; however, CACNA1F -associated disease (sometimes termed “incomplete” CSNB), which entails attenuation of both ON- and OFF-pathway signals, is also associated with myopia ( 25 ). Mechanisms driving myopia in the general population are likely to relate to more subtle aspects of the balance between ON- and OFF-pathway signaling, possibly at particular periods in development, rather than profound global attenuation of one pathway or the other.…”
Section: Discussionmentioning
confidence: 99%
“…1 In response to standard dark-adapted flashes (as defined by the International Society for Clinical Electrophysiology of Vision (ISCEV)), 1 2 an electronegative ERG usually indicates dysfunction occurring after phototransduction (eg, at the level of the photoreceptor synapse or bipolar cell). The finding of an electronegative ERG, particularly a normal-sized a-wave and reduced b-wave, is of clinical significance, [3][4][5]…”
Section: Introductionmentioning
confidence: 99%